Peran Kelompok Tani Bumi Lestari Kedoyo dalam Meningkatkan Kesejahteraan Peta - Langgeng Tri Wibowo; Sri Dwi Estiningrum (ACTIVA: Jurnal Ekonomi Syariah, 2021)
The agricultural sector has an important role in the economic development of a country. The contribution of the agricultural sector to the country's economic development lies in the provision of food and the occurrence of a larger and increasing food surplus for the entire community, encouraging the expansion of the secondary (industrial) and tertiary (services) sectors, increasing the country's foreign exchange earnings, increasing community and village income, and improve the welfare of society. As time goes by, the lives of farming communities in Indonesia are getting more attention with the initiative to establish an institution that aims to improve farmers' skills and improve the welfare of farmers through various agricultural activities that lead to modernity. This study aims to examine more deeply the role and constraints faced by the Bumi Lestari Kedoyo farmer group in an effort to improve the skills and welfare of farmers in Kedoyo Village both conventionally and prosperously according to Islam. This research uses qualitative research by conducting direct research to the field. This study uses a sampling technique with the Snowball Sampling technique and the data collection uses the method of observation, interviews and documentation to obtain accurate data. The results of this study indicate that farmers' welfare has been achieved conventionally and Islamically, but the existence of farmer groups has not been able to play a full role in improving farmers' welfare. This is due to the lack of awareness of farmers in participating in farmer group activities.